45‐4: Late‐News Paper: A Novel ADS Display Technology without Light Leakage. Issue 1 (25th September 2020) - Wang, Feifei; Zhan, Hongming; Shao, Xibin; Kang, Zhao; Huang, Hua; Ji, Lintao; Wang, Kaixuan; Chen, Xi; Wang, Zhangtao; Xue, Hailin; Yuan, Guangcai; Lin, Lifeng
Abstract : In the field of LCD, Advanced Super Dimension Switch (ADS) technology is widely used due to its outstanding features, such as high transmittance, wide view, and weak color shift. However, the ADS technology still has intractable problems. One of the most difficult problems is the dark state light leakage under mechanical deformation which is inherent in ADS. In this paper, a novel model called Zero Light Leakage ADS (ZLL‐ADS) is proposed, which can completely eliminate the dark state light leakage even under deformation. The key point of ZLL‐ADS is the introduction of +A plate in ADS panel. The important role of +A is to compensate the phase retardation of liquid crystals to avoid dark state light leakage caused by external stress on ADS panel. By applying ZLL‐ADS technology, the product properties of BOE's ADS Pro, especially the quality of the dark picture has been greatly improved, and the advantages of ADS in high transmittance and wide view are still maintained. The compensation principle is explained theoretically and verified by 18.5 inch FHD flat and curved demoes.